(untitled) (European Journal of Marketing and Economics, 2021)
One of the most important principles of civil process is the adversarial proceedings principle. This principle characterizes the civil process from its beginning in the trial in the court of first instance, in the court of appeal, until its conclusion in the High Court. Moreover, with the new changes that have been made in the civil procedural law, this principle finds application even before the beginning of the trial in the first instance. According to these changes, the party against whom the lawsuit is filed, before the trial against this party begins, has the right to present its claims against the lawsuit, in a document called “Declaration of defence”, leaving enough time for the fulfillment of this right for a period of 30 days. This scientific work will consist of tëo main issues. The first issue will address the meaning and importance of the adversarial proceedings principle in the civil process. In this issue, two different systems will be analyzed in the application of this principle, analyzing the advantages and disadvantages of each of them. The second issue will analyze the elements of the adversarial proceedings principle, looking at these elements in practical terms and the consequences that their non-implementation may bring. In this scientific work, the adversarial proceedings principle will be seen as part of the fair legal process provided by the Constitution of Albania and analyzed in several decisions of the Constitutional Court of Albania. This principle will also be addressed in the framework of international law, focusing on the way in which this principle is expressed in Article 6 of the European Convention on Human Rights and in the decisions of the Strasbourg Court regarding the fair legal process. At the end this scientific work will be given its conclusions, as well as the bibliography where this work is based.